2016
DOI: 10.3747/pdi.2014.00268
|View full text |Cite
|
Sign up to set email alerts
|

United Kingdom Survey of Culture-Negative Peritonitis and Dialysate Sampling Practice

Abstract: Peritonitis is a major cause of technique failure in peritoneal dialysis (PD) and accurate diagnosis ensures successful management and avoids unnecessary antibiotic exposure. United Kingdom (UK) registry data on peritonitis rates are not routinely reported. We conducted an electronic survey amongst senior PD nurses and microbiologists to obtain information about PD effluent sampling and processing practices in the UK. The survey was completed by 53 of 79 centres (67% response rate). The median annual culturene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Culture-negative peritonitis, as the name implies, is a case with clinical findings of peritonitis: abdominal pain, elevated peritoneal fluid WBCs, and peritoneal fluid cultures not growing a pathogen. Potential causes of culture-negative cases are antibiotic administration prior to peritoneal fluid cultures, suboptimal handling or processing of cultures or culture techniques, [59][60][61] or the presence of fastidious organisms, AFB, or filamentous fungi. Guidelines recommend a benchmark of less than 20% culture-negative cases.…”
Section: Culture-negative Peritonitismentioning
confidence: 99%
“…Culture-negative peritonitis, as the name implies, is a case with clinical findings of peritonitis: abdominal pain, elevated peritoneal fluid WBCs, and peritoneal fluid cultures not growing a pathogen. Potential causes of culture-negative cases are antibiotic administration prior to peritoneal fluid cultures, suboptimal handling or processing of cultures or culture techniques, [59][60][61] or the presence of fastidious organisms, AFB, or filamentous fungi. Guidelines recommend a benchmark of less than 20% culture-negative cases.…”
Section: Culture-negative Peritonitismentioning
confidence: 99%
“…Szeto et al 2 demonstrated that higher CNP rates were associated with sampling by a nonspecialist nurse and previous antibiotic exposure. In contrast, a UK survey 19 found no correlation between center-reported CNP rates and PDE processing technique, sampling volume, or center characteristics. In our study, CNP was associated with facilities that deviated from ISPD guideline recommendations concerning PDE preparation, collection, and handling, had limited facility resources (smaller hospital with no nephrologist on site), and had low facility experience (<100 PD cases).…”
Section: Discussionmentioning
confidence: 77%
“…Other pediatric studies report a range of culturenegative peritonitis rates from 11% to 67% (6-9). Among programs that care for adults on long-term PD, culturenegative rates range from 12% to 56%, with an average rate of 14%-16% among US centers (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%